2012
DOI: 10.1007/s00296-012-2482-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitude towards rheumatology training at foundation years’ level in the UK and rationale behind the students’ choice: results from a national survey

Abstract: The aims are to assess whether medical students are interested in rheumatology as a training post during post-medical-school and prior to specialty training that is covered by foundation years (FY) training in the UK, to determine the time spent in the undergraduate training in rheumatology and whether the desire for musculoskeletal (MsK) medicine training (rheumatology and orthopaedics taken together) is enhanced during FY training and to analyse the rationale behind their choice for rheumatology alone or com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thapper and Roussou have showed that exposure to rheumatology was the most important factor in the choice of a rheumatology rotation during foundation years. 6 Similarly, Wettoek et al showed that early exposure was the strongest predictive factor that may attract more students to consider rheumatology as a career. 7 The clinical training also improves the perception of rheumatology among students, as shown by Courties et al in a recent study.…”
Section: Discussionmentioning
confidence: 97%
“…Thapper and Roussou have showed that exposure to rheumatology was the most important factor in the choice of a rheumatology rotation during foundation years. 6 Similarly, Wettoek et al showed that early exposure was the strongest predictive factor that may attract more students to consider rheumatology as a career. 7 The clinical training also improves the perception of rheumatology among students, as shown by Courties et al in a recent study.…”
Section: Discussionmentioning
confidence: 97%
“…Recognition, diagnosis and management of paediatric rheumatic diseases poses challenges due to many factors (19). Non-paediatricians have limited training and understanding of growth, puberty, evaluation of paediatric pain, clinical care pathways, use of anti-rheumatic drugs in children, and the art of dealing with parents, school problems and transition into adulthood (7,(18)(19)(20)(21)(22)(23)(24).…”
Section: Knowledge Attitudes and Practices Towards Paediatric Rheumat...mentioning
confidence: 99%
“…1 Also, even the students give less importance to rheumatology and may not even feel they require training, unless they are specifically interested in the topic. 7 Rheumatoid arthritis is estimated to have a prevalence of 0.2-0.75% in India, with osteoarthritis having 5.8%, gout 0.12%, spondylarthritis having 0.1-0.2% and SLE having 3.2 out of 100,000. This means millions of undiagnosed patients are going without the needed medical care.…”
Section: Introductionmentioning
confidence: 99%